Case report: Immune pressure on hematopoietic stem cells can drastically expand glycosylphosphatidylinositol-deficient clones in paroxysmal nocturnal hemoglobinuria - Shingai, Naoki; Mizumaki, Hiroki; Najima, Yuho; Yamada, Yuta; Tran, Dung Cao; Haraguchi, Kyoko; Toya, Takashi; Okuyama, Yoshiki; Doki, Noriko; Nannya, Yasuhito; Ogawa, Seishi; Nakao, Shinji (Frontiers in Immunology, 2024)
Introduction: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare hematological disease characterized by intravascular hemolysis, thrombosis, and bone marrow (BM) failure. Although PNH is caused by excessive proliferation of hematopoietic stem cell (HSC) clones with loss of function mutations in phosphatidylinositol N-acetylglucosaminyltransferase subunit A (PIGA) genes, what drives PNH clones to expand remains elusive. Case description: We present a case of a 26-year-old female who presented with hemolytic anemia, thrombocytopenia, and leukopenia. Flow cytometry analysis of peripheral blood showed that 71.9% and 15.3% of the granulocytes and erythrocytes were glycosylphosphatidylinositol-anchored protein deficient (GPI[-]) cells. The patient was diagnosed with PNH with non-severe aplastic anemia. Deep-targeted sequencing covering 390 different genes of sorted GPI(-) granulocytes revealed three different PIGA mutations (p.I69fs, variant allele frequency (VAF) 24.2%; p.T192P, VAF 5.8%; p.V300fs, VAF 5.1%) and no other mutations. She received six cycles of eculizumab and oral cyclosporine. Although the patient’s serum lactate dehydrogenase level decreased, she remained dependent on red blood cell transfusion. Six months after diagnosis, she received a syngeneic bone marrow transplant (BMT) from a genetically identical healthy twin, following an immune ablative conditioning regimen consisting of cyclophosphamide 200 mg/kg and rabbit anti-thymocyte globulin 10 mg/kg. After four years, the patient’s blood count remained normal without any signs of hemolysis. However, the peripheral blood still contained 0.2% GPI (-) granulocytes, and the three PIGA mutations that had been detected before BMT persisted at similar proportions to those before transplantation (p.I69fs, VAF 36.1%; p.T192P, VAF 3.7%; p.V300fs, VAF 8.6%) in the small PNH clones that persisted after transplantation. Conclusions: The PNH clones that had increased excessively before BMT decreased, but persisted at low percentages for more than four years after the immunoablative conditioning regimen followed by syngeneic BMT. These findings indicate that as opposed to conventional theory, immune pressure on HSCs, which caused BM failure before BMT, was sufficient for PIGA-mutated HSCs to clonally expand to develop PNH.